Evaluation of the Regional Inflation Control Team's (TPID) Performance on the Medan City Economy - Siti Nurhalizah Lubis; Andri Soemitra (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
Inflation is a macroeconomic indicator which very important because it affects the value of money so the impact is directly felt by the public. In general, inflation is defined as a continuous increase in the public prices of an economy. Inflation is a symptom of rising prices that are general and take place continuously. Only a general increase in prices can be called inflation. An increase in the price of certain commodities due to seasonal factors, as an example ahead of big days or a temporary supply disruption and has no further effect, is not called inflation. This study evaluates the performance of the Regional Inflation Control Team (TPID) for the city of Medan.